Opioids in Urology: How Well Are We Preventing Opioid Dependence and How Can We Do Better? - Danyon J. Anderson; David Y. Cao; Jessica Zhou; Matthew McDonald; Abrahim N. Razzak; Jamal Hasoon; Omar Viswanath; Alan D. Kaye; Ivan Urits (Health Psychology Research)
Urologic procedures (both open and minimally invasive) can cause pain due to the surgery itself, devices placed, and post-operative issues. Thus, pain management is important for every post-procedure recovery period. Opioid use post-surgery is common and often over-prescribed contributing to persistent use by patients.